Bases for the theoretical foundation of neology and neologism: memory, attention and categorization - Lavale-Ortiz, Ruth M. (Círculo de Lingüística Aplicada a la Comunicación, 2019)
Neology currently has an important practical development, but theoretically reflections have not been reviewed since traditional studies. Our goal is to provide new data on its theoretical conception based on Cognitive Linguistics. Once highlighted the link between language and cognitive faculties (attention, memory, categorization), we conclude that the neological category can be structured in terms of prototypical effects where its elements are distributed flexibly in a continuum that reflects distinctions. In addition, it is shown that neologisms are subjective and relative entities, automatic figures that stand out over the discursive background in the attention process due to the surprise they generate; therefore, the psychological criterion is the natural method for its recognition. The theoretical reflection allows us to formulate axioms that should be considered in neological studies and to divide the understanding process of any neologism into three stages: recognition, interpretation and verification.
Keywords: Cognitive Linguistics; neological feeling; neology; neological verbs